A prospective clinical trial of the effects produced by the extrusion arch in the treatment of anterior open bite - Juliana de Brito Vasconcelos; Renata Rodrigues de Almeida-Pedrin; Thais Maria Freire Fernandes Poleti; Paula Oltramari; Ana Cláudia Ferreira de Castro Conti; Mirchel Henrique Bertola Bicheline; Steven J. Lindauer; Marcio Rodrigues de Almeida (SpringerOpen, 2020)
Abstract Aim To evaluate the maxillary dentition effects of the extrusion arch for anterior open bite (AOB) correction in mixed dentition patients. Materials and methods Fourteen subjects with an initial mean age of 9.17 ± 1.03 years presenting with dentoalveolar AOB (mean − 1.28 ± 1.46 mm) and normal facial pattern (FMA = 25.76°) were treated with an extrusion arch. The mean treatment period was 7.79 ± 2.58 months. Lateral cephalograms and dental models were taken before (T0) and after the correction of AOB (T1). Data were analyzed using paired t test to evaluate differences between T0 and T1. For all tests, a significance level of P < .05 was used. Results All patients achieved positive overbite at T1, with a mean increase of 3.07 mm. The maxillary incisors extruded 1.94 mm. Retroclination of the maxillary incisors (− 6.15°) and an increase in the interincisal angle (5.57°) were observed. There was a significant decrease in the distance between the incisal edge of the maxillary incisors and the molars (− 2.21 mm). There was significant mesial tipping of the maxillary molar (− 11.49°). Significant reductions of overjet (− 1.65 mm), arch perimeter (− 3.02 mm), and arch length (− 2.23 mm) were noted. The transverse maxillary intermolar distance did not change significantly. Conclusions The use of a maxillary extrusion arch was effective in the treatment of AOB. Overbite increased due to incisor extrusion, as well as retroinclination and overjet reduction. However, side effects, such as mesial molar tipping and decreases in arch perimeter and length might occur.